(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The research aims to evaluation of community potential enterprise in Phayao,Thailand. The research instrument was participation action research (PAR) andpotentially community questionnaires with key informants. The research instrument was participation action research (PAR) andpotentially community questionnaires. The study resultsthe community assessment of external and internal audit can be two parts; the procedure assessment was moderate level (x̄ = 2.15, SD. = 0.12), good organization management, a market management, knowledge management. In term of assessment outcome of audit was moderate level (x̄= 2.21, SD. = 0.05), the community was quality and service product, implement efficiency and development of community enterprise. And can be using for implementation of other community enterprise and value added to makingdecision for the local administration and local government.